Luminescent 3D printed poly(lactic acid) nanocomposites with enhanced mechanical properties - Kothavade, Premkumar Anil; Yadav, Prashant; Nidhankar, Aakash D.; Torris, Arun; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Sukumaran, Santosh Babu; Shanmuganathan, Kadhiravan (Polymer Engineering and Science, 2023)
The three-dimensional (3D) printing of functional composite materials has gained tremendous interest in recent years. Nevertheless, research on 3D printing of luminescent composite materials is very limited, and the mechanical properties of such 3D-printed composites are poor. Herein, we report the preparation and characterization of a poly(lactic acid) (PLA) composite that, when 3D printed, exhibits enhanced toughness and high solid-state fluorescence quantum yield. Incorporation of only 1 wt% pyrene butyric acid modified cellulose nanofibers (PBA-m-CNF) and l0 wt% thermoplastic polyurethane (TPU) into PLA led to 223% increase in toughness and 21% increase in tensile modulus of PLA. Scanning electron microscopy (SEM) and X-ray microcomputed tomography (mu-CT) analysis of the fractured cross-sections of 3D printed composites revealed a ductile failure mode. The PLA/PBA-m-CNF1/TPU10 3D printed composite also exhibited a high solid-state fluorescence quantum yield of 38.35%. To the best of our knowledge, this is the first report to show both enhanced mechanical properties and high solid-state fluorescence emission for 3D printable PLA. Such functional PLA composites could have potential applications in the fabrication of complex-shaped sensors, optical light pipes, etc.
Keywords: 3D printing; Composite; fluorescence; Nanocellulose; poly(lactic acid); toughness

Enhancing the crystallization kinetics and mechanical properties of poly(lactic acid) blends for 3D printing application - Kothavade, Premkumar; Yadav, Prashant; Gopal, Animesh; Pol, Harshawardhan; Kafi, Abdullah; Bateman, Stuart; Shanmuganathan, Kadhiravan (ACS Applied Polymer Materials, 2024)
3D printing of poly(lactic acid) (PLA) blends has been attempted to resolve issues such as inherent brittleness and slow crystallization rate of PLA. However, a persistent challenge remains in the form of phase separation or gradual migration of the blended soft polymer or plasticizers. To simultaneously enhance the miscibility of the blends and toughness of 3D-printed parts, a triblock copolymer PLA-PEG-PLA was synthesized and blended with PLA in varying proportions (5, 10, 15, and 20 wt %). Blending only 10-20 wt % low molecular weight PLA-PEG-PLA into PLA yielded a miscible blend that showed a 45-fold increase in elongation at break and a 23-fold enhancement in toughness over neat PLA. Scanning electron microscopy (SEM) images of fractured cross sections revealed a brittle to ductile transition in 3D-printed PLA/PLA-PEG-PLA samples. Isothermal crystallization studies and data analysis using the Avrami equation showed an enhancement in the crystal growth rate and overall rate of crystallization. The blends achieved half of their crystallinity in approximately 3 min, a significant improvement over the 9 min required by PLA alone. This underscores the efficiency of our approach. This was also evident in the spherulite growth of 3D-printed PLA and mPLA blends when examined using polarized optical microscopy (POM). To the best of our knowledge, this is the first report exploring the use of blends that include PLA and low molecular weight PLA-PEG-PLA triblock copolymers for 3D printing applications.
Keywords: Crystallization; FFF 3D printing; PLA-PEG-PLA triblock copolymer; poly(lacticacid); toughness

Extrusion 3D printing of intrinsically fluorescent thermoplastic polyimide: revealing an undisclosed potential - Kothavade, Premkumar; Kafi, Abdullah; Dekiwadia, Chaitali; Kumar, Viksit; Sukumaran, Santhosh Babu; Shanmuganathan, Kadhiravan; Bateman, Stuart (POLYMERS, 2024)
Keywords: Additive manufacturing; functional extrusion; high-performance polymers; thermoplastic polyimide